A Multicenter Analysis of Factors Associated With Apixaban-Related Bleeding in Hospitalized Patients With End-Stage Renal Disease on Hemodialysis. (November 2017) - Steuber, Taylor D.; Shiltz, Dane L.; Cairns, Alex C.; Ding, Qian; Binger, Katie J.; Courtney, Julia R.
Background: In 2014, the United States Food and Drug Administration approved a labeling change for apixaban to include recommendations for patients with severe renal impairment and patients with end-stage renal disease (ESRD) on hemodialysis (HD), though these recommendations are largely based on pharmacokinetic and pharmacodynamic data.Objective: Identify variables associated with bleeding events in hospitalized patients with ESRD on HD receiving apixaban.Methods: This retrospective, multicenter cohort study evaluated hospitalized patients with ESRD on HD receiving apixaban from January 1, 2013, through March 31, 2016. Correlational analysis and logistic regression were completed to identify factors associated with bleeding.Results: A total of 114 adults were included in the analysis. The median length of stay (LOS) was 6.2 (interquartile range = 3.8-11.9) days and bleeding events occurred in a total of 17 patients (15%). A weak correlation was identified for higher cumulative apixaban exposure, increased number of HD sessions while receiving apixaban, and increased hospital LOS ( P < 0.05; correlation coefficient < 0.40). When controlling for confounders, logistic regression revealed that composite bleeding events were independently increased by continuation of outpatient apixaban (odds ratio = 13.07; 95% CI = 1.54-110.54; P = 0.018), increased total daily dose of apixaban (odds ratio = 1.72; 95% CI = 1.20 to 2.48; P = 0.003), and total HD sessions while receiving apixaban (odds ratio = 2.04; 95% CI = 1.06-3.92; P = 0.033).Conclusion: The association between these factors and increased bleeding should prompt concern for long-term anticoagulation with apixaban in patients with ESRD receiving chronic HD.